The Influence of Collaborative Learning Environment on Motivation and Learning Outcomes of Elementary School Students - Isna'atul Rizqi Kusumawardan (PT. AVID MEDIA INDONESIA, 2026)
A collaborative learning environment is considered a relevant learning approach for improving the quality of elementary school education. This study aims to describe the influence of a collaborative learning environment on the motivation and learning outcomes of elementary school students through a deeper understanding of the learning process. A qualitative approach with a descriptive design was used to explore the dynamics of learning interactions, student experiences, and the role of teachers in creating a collaborative learning environment. The research subjects consisted of elementary school teachers and students actively involved in group-based learning. Data collection techniques were carried out through learning observations, in-depth interviews, and documentation studies, then analyzed using an interactive analysis model. The results showed that a collaborative learning environment encourages positive social interactions, increases learning engagement, and strengthens students' intrinsic motivation. Continuously developing learning motivation contributes to improved learning outcomes, both in cognitive, affective, and social skills. Collaborative learning also builds students' self-confidence, critical thinking skills, and cooperative attitudes. The teacher's role as a facilitator is an important factor in maintaining the effectiveness of a collaborative learning environment. This study concludes that the implementation of a collaborative learning environment has the potential to comprehensively improve the quality of learning processes and outcomes in elementary schools